The relationship of genetic risk factors with the development of arterial hypertension taking into account ethnic differences - A. Ya. Kovaleva; N. V. Kokh; E. N. Voronina; O. S. Donirova; E. M. Zelenskaya; G. I. Lifshits (Российский кардиологический журнал, 2019)
Aim. To study the influence of genetic factors on the risk of essential arterial hypertension (AH) and the course in patients of Russian and Buryat ethnicity.Material and methods. The study included 248 patients of the Russian and 92 patients of the Buryat ethnic group. All patients were evaluated for genotypes by ACE, ADRB1, ADRB2, ADRB3, CAT, NOS3, CYP11B2, AGT, STK39, EDN1, GNB3 markers. Following clinical data were determined: age, body mass index, smoking history, stage and degree of AH, the presence and nature of target organ damage, hereditary history. In the study, patients of the two ethnic groups were divided into the case and control groups depending on the presence or absence of AH.Results. In patients of the Russian ethnic group, an association of a more severe AH course with a burdened family history was revealed, in contrast to patients of Buryat nationality. In the Buryat group, the development of AH is associated with polymorphisms of the candidate genes ADRB3 (rs4994), GNB3 (rs5443), ACE (rs464994), STK39 (rs3754777), EDN1 (rs9349379). In the Russian group, ACE, EDN1, CYP11B2 (rs 1799998), GNB3, NOS3 (rs1799983), ADRB1 (rs1801253) genes had a significant contribution. When comparing the assortment of allele frequency of the ACE gene polymorphic marker among two ethnic groups, the “I” allele was found significantly more frequently in patients of Russian group.Conclusion. The results of the study revealed ethnic differences in the genetic features of essential AH. For the first time, an association between genetic markers encoding elements of the renin-angiotensin system, sympathoadrenal system, endothelial system and AH risk in patients of Buryat nationality was established. The identification of ethnic differences and genetic predisposition to AH, makes it possible to understand the role of the hereditary component of hypertension. We suppose that these data in conjunction with the influence of the environment, can help to develop one of the areas of personalized medicine.